The Role of The Teacher in Managing The Social-Emotional Abilities of Early Childhood - Azzahra Fadila Rahma; Isnaini Budi Hastuti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Early childhood education, particularly during the 'golden age' of 5-6 years, often lacks balance. Emphasis is placed on academic aspects such as recognizing numbers and letters, while crucial social-emotional development, essential for shaping personality and life skills, is neglected. Consequently, children struggle to comprehend lessons when emotions are unmanaged and are prone to social issues like conflicts or isolation. This study aims to analyze how teachers manage social-emotional skills in 5-6-year-olds and provide practical guidelines for integrating social-emotional education into daily learning. Employing a qualitative descriptive method at TK Aisyiah 3 Jogorogo, with two teachers as subjects, data were collected via direct observations of child behavior and in-depth interviews over one month. Data were then evaluated using thematic analysis to identify key themes, such as patterns of child interaction and teachers' roles as role models. Findings reveal teachers understand child development through daily observations, such as during peer interactions or challenges. They address this by fostering a safe classroom environment, modeling emotional regulation, designing collaborative activities like team games to build empathy and emotional control, and collaborating with parents for consistency between home and school. In conclusion, teachers play a central role in shaping children's emotional intelligence through holistic approaches, including balanced digital education integration and teaching skills like breathing techniques for self-calming. Thus, children develop into stable, empathetic individuals ready for life's challenges, ensuring education encompasses not only academics but also vital social-emotional aspects.